PENGUASAAN KOSA KATA DENGAN MENULIS TEKS ANEKDOT CERITA PENDIDIKAN PADA SISWA - Abdullah Hasibuan, Nirmawan (PUSKAPAD, 2022)
The vocabulary is very important for every individual to speak skillfully. Therefore, each individual must require a vocabulary for communicating with other individuals. Without language communication can not be done well.In the teaching of writing of schools often we find that students are less capable in terms of mastery of vocabulary will have difficulties in making or completing a writing. This study aims to determine the mastery of vocabulary possessed in writing poetry class X student of SMAN 2 Tanjungbalai Year of Education from 2018-2019. The study population was all students of class X SMAN 6 Tanjungbalai as many as 63 people. Because the number of students who exist in a population of less than 100 people, the samples taken as many as 63 people. The method used in this research is descriptive method.The instrument used was a write Anecdote text. Based on the data processing obtained average value is the ability to write Anecdote text score of 88.65 out of 100. Thus, it can be said that the average value of the ability to write poetry with the mastery of vocabulary can be categorized as very good score range between 85-100. Based on data analysis can be concluded that the mastery of vocabulary in writing has been very good and developing aspects of the theme, diction (word choice), the style of presentation and message / mandate owned by a class X students of SMAN 6 Tanjungbalai Year of Education from 2018 to 2019.